Penerapan Metode Drill dalam Meningkatkan Kemampuan Menghafal Al-Qur’an di SD Negeri 12 Rokan IV Koto - Mustapa, Mustapa; Mastrio, Mastrio; Nurazmi, Nurazmi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to analyze the implementation of the drill method in improving students’ Qur’an memorization skills at SD Negeri 012 Rokan IV Koto. The research employs a Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, consisting of four stages in each cycle: planning, action implementation, observation, and reflection. Data were collected through observations, interviews, questionnaires, and document analysis. The data were analyzed using a qualitative descriptive approach through data reduction, data presentation, and conclusion drawing. The findings indicate that the gradual implementation of the drill method effectively enhances students’ memorization skills. In the first cycle, student participation increased, although some still struggled to retain their memorization. In the second cycle, students showed significant improvements in fluency and accuracy. Additionally, questionnaire results revealed that the drill method increased students’ motivation in learning the Qur’an. However, the study also identified challenges, such as the need for more intensive teacher guidance and the variation of methods to maintain student interest. Therefore, schools need to provide adequate facilities and support teachers in developing effective drill-based teaching strategies.